2019
DOI: 10.1148/radiol.2018180950
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Wave Elastography of Benign versus Malignant Musculoskeletal Soft-Tissue Masses: Comparison with Conventional US and MRI

Abstract: To examine if shear-wave elastography (SWE) improves the accuracy of diagnosing soft-tissue masses as benign or malignant compared with US alone or in combination with MRI. Materials and Methods: Two hundred six consecutive adult participants (mean age, 57.7 years; range, 18-91 years), including 89 men (median age, 56.0 years; range, 21-91 years) and 117 women (median age, 59.1 years; range, 18-88 years), who were referred for biopsy of a soft-tissue mass were prospectively recruited from December 2015 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
5
25
0
Order By: Relevance
“…Interestingly, the unit of shear wave velocity (m/s) yielded better results across all outcomes in comparison to stiffness (kPa). This is in agreement with two previous studies that reported a lower reliability for kPa as a result of the mathematical conversion, which depends on pixel averaging meaning that pixel heterogenicity can lead to differing stiffness calculations for the same measured velocity [14,22]. We therefore support the use of shear wave velocity as a surrogate for tissue elasticity when imaging soft tissue masses as this should ensure better repeatability as evidenced in our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the unit of shear wave velocity (m/s) yielded better results across all outcomes in comparison to stiffness (kPa). This is in agreement with two previous studies that reported a lower reliability for kPa as a result of the mathematical conversion, which depends on pixel averaging meaning that pixel heterogenicity can lead to differing stiffness calculations for the same measured velocity [14,22]. We therefore support the use of shear wave velocity as a surrogate for tissue elasticity when imaging soft tissue masses as this should ensure better repeatability as evidenced in our results.…”
Section: Discussionsupporting
confidence: 92%
“…Adult patients (n = 64) were consecutively referred through local sarcoma services over a 12-month period between March 2016 until March 2017, with no clinical exclusion criteria. The patients in this study were involved in a larger study of imaging characteristics and elastography in benign and malignant masses [22]. Patients were retrospectively selected where five individual elastography readings had been recorded.…”
Section: Patient Populationmentioning
confidence: 99%
“…Still, no guidelines are currently available for the use of elastography in musculoskeletal cancer diagnostics. Furthermore, of the currently published studies, many use quantitative shear wave elastography instead of strain elastography, with methods not directly comparable to those of the current study [20].…”
Section: Discussionmentioning
confidence: 99%
“…39 With regard to soft tissue masses, shear-wave elastography can increase the accuracy of diagnosis in conjunction with gray-scale US. 40 However, no useful threshold in shear-wave velocity was found to differentiate benign from malignant lesions. 40,41 A positive correlation was found between shearwave velocities assessed along the long and short axes of the soft tissue mass.…”
mentioning
confidence: 99%
“…40 However, no useful threshold in shear-wave velocity was found to differentiate benign from malignant lesions. 40,41 A positive correlation was found between shearwave velocities assessed along the long and short axes of the soft tissue mass. 41…”
mentioning
confidence: 99%